The endocannabinoid transport inhibitor AM404 differentially modulates recognition memory in rats depending on environmental aversiveness - Campolongo, Patrizia; Ratano, Patrizia; Manduca, Antonia; Scattoni, Maria Luisa; Palmery, Maura; Trezza, Viviana; Cuomo, Vincenzo (Frontiers in Behavioral Neuroscience, 2012)
Cannabinoid compounds may influence both emotional and cognitive processes depending on the level of environmental aversiveness at the time of drug administration. However, the mechanisms responsible for these responses remain to be elucidated. The present experiments investigated the effects induced by the endocannabinoid transport inhibitor AM404 (0.5-5 mg/kg, i.p.) on bothemotional and cognitive performances of rats tested in a Spatial Open Field task and subjected to different experimental settings, named High Arousal and Low Arousal conditions. The two different experimental conditions influenced emotional reactivity independently of drug administration. Indeed, vehicle-treated rats exposed to the Low Arousal condition spent more time in the centre of the arena than vehicle-treated rats exposed to the High Arousal context. Conversely, the different arousal conditions did not affect the cognitive performances of vehicle-treated animals such as the capability to discriminate a spatial displacement of the objects or an object substitution. AM404 administration did not alter the locomotor activity of the animals exposed to both environmental conditions. Interestingly, AM404 administration increased the emotional reactivity of rats exposed to the High Arousal condition but did not influence emotionality of rats exposed to the Low Arousal condition. Moreover, AM404 administration influenced the cognitive parameters depending on the level of emotional arousal: it impaired the capability of rats exposed to the High Arousal condition to recognize a novel object while it did not induce any impairing effect in rats exposed to the Low Arousal condition. These findings suggest that drugs which enhance the endocannabinoid signalling induce different effects on recognition memory performance depending on the level of emotional arousal induced by the environmental conditions.